Antecedents and consequences of employee engagement: empirical study of hotel employees and managers - Lee, JungHoon (Kansas State University, 2012)
Employee engagement has received a great deal of attention in the last decade in the popular business press and among consulting firms and the practitioner community. They claim employee engagement is a new human resource practice that business organizations can use in order to cope with the uncertainty of turbulent industry conditions. However, in the academic community, the concept remains new, and therefore, the concept requires rigorous seminal studies to validate it. Given that practical interest in work engagement has outstripped the currently available research evidence, fundamental questions, like how it can be increased and how and why it benefits individuals and organizations, still require answers. Therefore, this study empirically tested relationships among antecedents and consequences of employee engagement in the hotel setting. In particular, this study provided theory-based empirical evidence regarding whether employee evaluations of self (i.e., core self-evaluations) and perceptions of organizational environment (i.e., psychological climate) affect employee engagement. This study also investigated how employee engagement directly and indirectly leads to intrinsic rewards, job satisfaction, personal attachment to an organization (i.e., organizational commitment), and the leader-member exchange relationship (LMX). In accordance with the purpose and objectives of the study, 11 hypotheses were proposed based on several theories: Kahn's three psychological conditions theory, job demands-resources model, social exchange theory, and conservation of resources theory. To test the hypotheses, data were collected from 394 hotel employees and managers in the United States. The proposed relationships were examined using hierarchical multiple regression and structural equation modeling. Results of hypothesis testing showed that core self-evaluations and three components of psychological climate (managerial support for service, interdepartmental service, and team communication) positively influence employee engagement. The results also revealed that employee engagement is positively associated with all the outcome variables. This study further demonstrated that LMX mediates the relationships of employee engagement with job satisfaction and organizational commitment; job satisfaction mediates the relationships between employee engagement and organizational commitment and between LMX and organizational commitment. Given that employee engagement is an important current issue for hospitality companies, the findings should provide the hotel industry with a more complete picture of how employee engagement is associated with its antecedents and outcomes. A discussion of managerial implications is included along with theoretical implications of the findings, an evaluation of research limitations, and directions for future research.
Keywords: Employee engagement; Core self-evaluation; Psychological climate; Job satisfaction; Leader-member exchange; Organizational commitment; Behavioral Sciences (0602); Business (0310); Organizational Behavior (0703)